Genetic Variability of Koi Herpesvirus In vitro—A Natural Event? - Klafack, Sandro; Wang, Qing; Zeng, Weiwei; Wang, Yingying; Li, Yingying; Zheng, Shucheng; Kempter, Jolanta; Lee, Pei-Yu; Matras, Marek; Bergmann, Sven M. (Frontiers in Microbiology, 2017)
Worldwide koi herpesvirus (KHV) causes high mortalities in Cyprinus carpio L. aquaculture. So far, it is unknown how the different variants of KHV have developed and how they spread in the fish, but also in the environmental water bodies. Therefore, a phylogenetic method based on variable number of tandem repeats (VNTR) was improved to gain deeper insights into the phylogeny of KHV and its possible worldwide distribution. Moreover, a VNTR-3 qPCR was designed which allows fast virus typing. This study presents a useful method for molecular tracing of diverse KHV types, variants, and lineages.